PURPOSE SOFTWARE SYSTEM FOR COMMUNICATION NETWORK OPERATING DATA - Syahril sy Syahril (Majalah SIKOMTEK, 2010)
Data communication can be developed through the propagation of radio waves. Data communication via radio is able to overcome the problem of limited telecommunication facilities in remote areas who have limited means of communication. In general, data communication can be said as the process of sending data or information which have been modified in a certain code (convert it into electrical signals) and data is transmitted. Transmission medium can be via satellite (VSAT-Very Small apertures Terminal), telephone cable, or via radio waves (HF / VHF / UHF).